Apology of Subjectivity, in Science and Social Relations (Global Journal of Human-Social Science, 2023)
A subjectivity is the confessed manifestation of a created social coexistence or interrelation of individuals that is socially integrated to reproduce and produce its development possibilities production that is represented by a subject a phenomenon commonly known eventually as subjectivity which is nothing more than the social representation of a construction through an individual who represents an active social integration or intersubjectivity therefore subjectivity is not a simple opinion as an isolated definition of an individual it is rather a manifest intersubjectivity or represented by a subject of a social unit in interaction being that this as a created social manifestation is an ideal reproduction of conditions of a developing coexistence that has built as a process subjects that manifest the experiences produced as part of a social integration or intersubjectivity that is created o constantly produced as definitions of reproduction and social development Hence a subjective manifestation is a represented intersubjectivity that is a subject as a social individual only is insofar as a state to be from its manifestation or represented social interrelation that allows it to be and transcend as a representative of a collectivity Hence subjectivity is the demonstrative graphic representation of a community from a collective construction to which it represents or applies through an individual manifestation that reproduces variable and complex - depending on the different types of coexistence- matrices of social development to prevent and act in their social interaction with others which means defining subjectivity as a created social product where a subject represents a plurality of interrelations produced and in production a process that this article will deal with as part of a hermeneutic methodical relationship that pretends or rather presumes to understand such interrelationship
Keywords: subjectivity; subject; intersubjectivity; experience; science; representation; interaction; consciousness; being